2015
DOI: 10.1113/jp270914
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory respiratory responses to progesterone and allopregnanolone in newborn rats chronically treated with caffeine

Abstract: Key pointsr In premature newborns, recurrent apnoea is systematically treated with caffeine to prevent long-term neurocognitive disorders, but a substantial percentage of apnoea persists particularly in neonates born before 28 weeks of gestation.r Progesterone has been proposed as a respiratory stimulant potentially suitable for the treatment of newborn apnoea persistent to caffeine. Accordingly we asked whether acute progesterone administration reduces apnoea frequency in newborn rats treated with caffeine.r … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 62 publications
(153 reference statements)
0
20
0
1
Order By: Relevance
“…; Uppari et al . ). For these experiments, progesterone was given at 4 mg kg −1 once a day between 08.00 and 09.00 h between postnatal days 3 and 12 [gavage volume: 0.05 ml (10 g body weight) −1 ].…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…; Uppari et al . ). For these experiments, progesterone was given at 4 mg kg −1 once a day between 08.00 and 09.00 h between postnatal days 3 and 12 [gavage volume: 0.05 ml (10 g body weight) −1 ].…”
Section: Methodsmentioning
confidence: 97%
“…; Uppari et al . ). Briefly, fresh air flowing through the chamber was set at 180 ml min −1 , and the temperature inside the chamber was maintained at 30°C using a temperature control system (TCAT‐2; Physitemp, Clifton, NJ, USA).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…potentiates the inhibitory action of GABA on basal respiratory activity (Uppari, Joseph, & Bairam, 2016); an observation that was less evident in female rats . Subsequent work by the same group showed that the stimulatory effects of acute caffeine administration become more important with age.…”
Section: Discussionmentioning
confidence: 90%